2015
DOI: 10.1021/acs.inorgchem.5b00735
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydrolytic Studies on the Air-Stable [(4-CN-PhO)(E)P(μ-NtBu)]2 (E = O, S, and Se) Cyclodiphosphazanes

Abstract: Reaction of 4-CN-PhOH with [ClP(μ-N(t)Bu)]2 (1) (2:1 ratio) in the presence of Et3N produced the functionalized cyclodiphosph(III/III)azane [(4-CN-PhO)P(μ-N(t)Bu)]2 (2). Oxidation of 2 produced cyclodiphosph(V/V)azanes [(4-CN-PhO)(E)P(μ-N(t)Bu)]2 [E = O (3), S (4), and Se (5)]. This is the first example of a series of cyclodiphosph(V/V)azane derivatives obtained from a single cyclophosph(III/III)azane precursor where all the accessible chalcogen oxidized products are air-stable over prolonged periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 69 publications
6
29
0
Order By: Relevance
“…The presence of m-S bridging atoms in 2 and cisoid geometry with respectt ot he P 2 N 2 rings makes it an ideal donor for metal coordination. (1) , respectively) are similar to those found in the precursor [(S= )ClP(m-NtBu)] 2 (1) [4] (1.996 (3) ). However, as expected there is as ignificante longation of the PÀSbonds by 0.07-0.08 int he [SÀP(Cl)(m-NtBu)] 2 2À dianion in 3 and 4 (1.987(6) a nd 1.989(3) , respectively) compared to the P=Sb ond length in 1 [1.911 (2) ],c onsistentw ith the reduction of the double bond to as ingle bond.…”
Section: Resultssupporting
confidence: 77%
“…The presence of m-S bridging atoms in 2 and cisoid geometry with respectt ot he P 2 N 2 rings makes it an ideal donor for metal coordination. (1) , respectively) are similar to those found in the precursor [(S= )ClP(m-NtBu)] 2 (1) [4] (1.996 (3) ). However, as expected there is as ignificante longation of the PÀSbonds by 0.07-0.08 int he [SÀP(Cl)(m-NtBu)] 2 2À dianion in 3 and 4 (1.987(6) a nd 1.989(3) , respectively) compared to the P=Sb ond length in 1 [1.911 (2) ],c onsistentw ith the reduction of the double bond to as ingle bond.…”
Section: Resultssupporting
confidence: 77%
“…[35,41,42] Next, we explored the use of functionalised organic acids( e.g.,c yano, ester,e tc.) Often, these functionalised acids are only sparingly soluble in most solvents that are chemically compatible with compound 1.M illing compound 1 with 4-aminopyridine in the presence of Et 3 Na saBrønsted base (1:2:2 molar ratio) for three hours in aR etsch MM400 mixer mill operating at 30 Hz loaded with a1 0mms tainless steel ball (4 gw eight) successfully generated compound 2,asevidenced by the 31 P{ 1 H} nuclear magnetic resonances pectrumo ft he crude sample.…”
Section: Acyclic Disubstituted Cyclodiphosphazanesmentioning
confidence: 99%
“…Furthermore, an increased stability of the P-N framework upon oxidation of the phosphorus center has been reported. 9 For example, Balakrishna et al reported the synthesis of a series of cyclophosph(V/V)azanes showing enhanced air and moisture stability. 10 These results prompted us to investigate the stability of cyclic cyclophosphazane cage frameworks of the type [{P(m-NR)} 2 (m-NR)] 2 [R = t Bu (1) and i Pr (3)] upon oxidation.…”
mentioning
confidence: 99%